1979
DOI: 10.1038/hdy.1979.38
|View full text |Cite
|
Sign up to set email alerts
|

A gene that modifies the sex ratio in a bisexual strain of Sciara ocellaris

Abstract: SUMMARYThe influence of an X-linked recessive mutation, sepia, on the sex determination of a bisexual strain of Sciara ocellaris was studied. It induces an alteration in the sex ratio, especially in the progeny of heterozygous females, increasing the proportinn of males. These results cannot be explained by differential fecundity of the female parents of different genotypes nor by differential mortality between the sexes. The occurrence of gynandromorphs indicates that the mutant probably interferes with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…In this species the offspring are composed of male and female individuals, but the sex ratio varies widely (Metz, 1938;Davidheiser, 1943;Mori et al, 1979). It has been shown that this variation depends on temperature: at 18-20°C, the sex ratio distribution, although variable, shows a median at approximately 50%, but at 24-29°C the sex ratio moves towards the production of more females.…”
Section: Sex Determination Mechanisms Based On X Chromosome Eliminatimentioning
confidence: 99%
“…In this species the offspring are composed of male and female individuals, but the sex ratio varies widely (Metz, 1938;Davidheiser, 1943;Mori et al, 1979). It has been shown that this variation depends on temperature: at 18-20°C, the sex ratio distribution, although variable, shows a median at approximately 50%, but at 24-29°C the sex ratio moves towards the production of more females.…”
Section: Sex Determination Mechanisms Based On X Chromosome Eliminatimentioning
confidence: 99%
“…We used an amphigenic strain of Sciara ocellaris that has been maintained in the laboratory since 1965 (Pavan and Perondini, 1967) and which has a progeny sex-ratio varying from a few males to a preponderance of males (Mori et al, 1979). In our investigation the number of flies produced by each female also varied widely, from progenies with only a few flies (progenies with less than 30 flies were not used) to progenies with 185 flies.…”
Section: Fly Strainmentioning
confidence: 99%
“…However, whereas in S. coprophila females produce only either female-producer or male-producer oocytes, in S. ocellaris each female generates both classes of oocytes. Thus, in this species the offspring of each female is composed of males and females, although the sex ratio varies widely among the females (Metz 1938;Davidheiser 1943;Mori et al 1979). This variation depends on temperature: at 18-20…”
Section: The Digenic Species Sciara Ocellarismentioning
confidence: 99%
“…A strain of S. ocellaris has been described that carries sepia(s)-X chromosome (an X chromosome that carries the sepia mutation as a marker) that causes alterations in the sex ratio towards the production of more males, without differential mortality of female embryos (Mori et al 1979). Moreover, the offspring of this strain contain as well a significant number of gynandromorphs (individuals with some portions of the body typically male X0 and others typically female XX); i.e., individuals in which some somatic nuclei eliminate only one and other nuclei eliminate both two paternal-derived X chromosomes ( Mori et al 1979;Mori and Perondini 1980).…”
Section: The Digenic Species Sciara Ocellarismentioning
confidence: 99%